Remineralizing potential of synthetic saliva: an in vitro study - Huanambal Tiravanti, Victor Abel (2024)
Objective: To evaluate the remineralizing effect of synthetic saliva on eroded bovine dental enamel. Materials and methods: 50 enamel blocks were prepared from bovine teeth. The specimens were divided into 5 study groups according to treatment: group A (Colgate Total®, toothpaste containing fluoride), group B (MI Paste Plus®, toothpaste containing casein phosphopeptide, amorphous calcium phosphate [CPP-ACP] with fluoride), group C (Salival® Solution, synthetic saliva), group D (distilled water) and group E (no treatment). All specimens in groups A, B, C and D received 0.5% citric acid attacks for 2 minutes at 0, 8, 24 and 32 hours. After each acid attack, toothpastes corresponding to each treatment group were applied. The degree of mineralization was then evaluated by Raman microscopy and surface microhardness by Vickers microhardness. Results: Regarding the degree of mineralization and surface hardness, no significant differences (p > 0.05) were found in the eroded bovine tooth enamel treated with Colgate Total®, Mi Paste Plus® and Salival® Solution in comparison with the healthy enamel samples. But all presented a significantly higher degree of mineralization and surface hardness than the eroded bovine tooth enamel samples preserved in distilled water (p < 0.05). Conclusion: This in vitro study shows that the synthetic saliva Salival® Solution has a remineralizing potential on eroded bovine enamel.